Point Mutation of a Non-Elastase-Binding Site in Human α1-Antitrypsin Alters Its Anti-Inflammatory Properties - Lior, Yotam; Zaretsky, Mariana; Ochayon, David E.; Lotysh, Diana; Baranovski, Boris M.; Schuster, Ronen; Guttman, Ofer; Aharoni, Amir; Lewis, Eli C. (Frontiers in Immunology, 2018)
Introduction: Human alpha1-antitrypsin (hAAT) is a 394 aa-long anti-inflammatory, neutrophil elastase inhibitor, that binds elastase via a sequence-specific molecular protrusion (reactive center loop, RCL; positions 357-366). hAAT formulations that lack protease inhibition were shown to maintain their anti-inflammatory activities, suggesting that some attributes of the molecule may reside in extra-RCL segments. Here, we compare the protease-inhibitory and anti-inflammatory profiles of an extra-RCL mutation (cys232pro) and two intra-RCL mutations (pro357cys, pro357ala), to naïve (WT) recombinant hAAT, in vitro and in vivo. Methods: His-tag recombinant point-mutated hAAT constructs were expressed in HEK-293F cells. Purified proteins were evaluated for elastase inhibition, and their anti-inflammatory activities were assessed using several cell-types: RAW264.7 cells, mouse bone marrow-derived macrophages and primary peritoneal macrophages. The pharmacokinetics of the recombinant variants and their effect on LPS-induced peritonitis were determined in vivo. Results: Compared to WT and to RCL-mutated hAAT variants, cys232pro exhibited superior anti-inflammatory activities, as well as a longer circulating half-life, despite all three mutated forms of hAAT lacking anti-elastase activity. TNFα expression and its proteolytic membranal shedding were differently affected by the variants; specifically, cys232pro and pro357cys altered supernatant and serum TNFα dynamics without suppressing transcription or shedding. Conclusion: Our data suggest that the anti-inflammatory profile of hAAT extends beyond direct RCL regions. Such regions might be relevant for the elaboration of hAAT formulations, as well as hAAT-based drugs, with enhanced anti-inflammatory attributes.